ANALISIS PEMBIAYAAN MUSYARAKAH TERHADAP LABA BERSIH PADA PT BANK MUAMALAT INDONESIA - Hamidi, Hamidi (MEASUREMENT, 2014)
Research on Musyarakah financing Against Net Profit at PT Bank Muamalat Indonesion, aims to determine how the results of Musyarakah financing to net income in its capital, research also aims to determine how the relationship to the results of Musharaka financing to net income on bank mualamat Indonesia. The object of this research is PT Bank Muamalat this Indonesia.Penelitian using descriptive qualitative analysis of the overall outlines the results of Musharaka financing to net income on bank Muamalat Indonesia in comparison with theory - the theory relating to the results of Musyarakah Â financing terladap net income on bank Muamalat, so that in can result diingikan ini.Teknik research data collection techniques used are keperpustakaan, field research. Fieldwork was carried out by means of observation and interviews, while the literature research was obtained from the material - material available in books - books, lecture notes and other reading materials related to the research.Based Â on the research and discussion, the authors conclude that the Musyarakah financing to net income that there is a significant relationship between Musharaka financing with net income on its capital. If the correlation coefficient of 0.953 visits, so it can be concluded that there is a very strong and positive values between Musyarakah financing with net income on its capital.